DIHYDROPYRIDINE CALCIUM ANTAGONISTS: THE ROLE IN CURRENT THERAPY OF CARDIO-VASCULAR DISEASES - E. V. Shilova; S. Y. Martsevich (Рациональная фармакотерапия в кардиологии)
Classification of calcium antagonists (CA) is presented. Results of the large clinical trials (STONE, STOP-Hypertension-2, ALLHAT, ASCOT-BPLA etc.) devoted to estimation of CA effects on the risk of cardiovascular complications are analyzed. The significant place of dihydropyridine CA in current guidelines on arterial hypertension and ischemic heart disease therapy is underlined. Results of a pilot study on comparison of two amlodipines (original Norvasc and generic Stamlo M) are discussed.